Aide au suivi du phénomène de dénitrification naturelle pour une gestion durable de la ressource en eau du Béthunois - José Luis Martin-Bordes; Éric Henry; Cherif Boulemia; François-Xavier Masson (Développement Durable et Territoires)
Cities face a substantial increase in population and in industrial activities which entails an increasing demand for water. Our aim is to develop a management and decision-making framework for a better knowledge of the resource and to support the planning and decisions in the water boards of medium-size local communities. The framework will allow the reasoned exploitation of the aquifer system and in particular the preservation of the natural denitrification process which occurs in the chalk aquifer in the Béthunois area in northern France. In this article, we propose the setting-up of a control panel thanks to a GIS platform coupled with a hydrological model. Our research work is applied to the SIVOM of the Béthunois.